2017
DOI: 10.1523/jneurosci.1376-17.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Rodent Medial Frontal Control of Temporal Processing in the Dorsomedial Striatum

Abstract: Although frontostriatal circuits are critical for the temporal control of action, how time is encoded in frontostriatal circuits is unknown. We recorded from frontal and striatal neurons while rats engaged in interval timing, an elementary cognitive function that engages both areas. We report four main results. First, "ramping" activity, a monotonic change in neuronal firing rate across time, is observed throughout frontostriatal ensembles. Second, frontostriatal activity scales across multiple intervals. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
202
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(274 citation statements)
references
References 76 publications
39
202
4
Order By: Relevance
“…As in our past work, GLMM analyses revealed that DMS firing rates were affected by optogenetic stimulation (F = 8.3, p = 0.0003; see Table 2 for stats) and time in the interval (i.e., time-related ramping; F = 333.7, p = 1e -74 ). Of note, there was an interaction between MFC inactivation and firing rates over time (F = 35.6, p = 2e -9 ) 13 and between MFC inactivation and optogenetic stimulation of MFCàDMS axons (F = 5.5, p = 0.004, Table 2). Importantly, our model indicated that there was an interaction between time, optogenetic stimulation, and MFC inactivation (F = 11.4, p = 0.00001; Table 2).…”
Section: Optogenetic Stimulation Of Mfc Axons In Dms Alters Time-depementioning
confidence: 98%
See 4 more Smart Citations
“…As in our past work, GLMM analyses revealed that DMS firing rates were affected by optogenetic stimulation (F = 8.3, p = 0.0003; see Table 2 for stats) and time in the interval (i.e., time-related ramping; F = 333.7, p = 1e -74 ). Of note, there was an interaction between MFC inactivation and firing rates over time (F = 35.6, p = 2e -9 ) 13 and between MFC inactivation and optogenetic stimulation of MFCàDMS axons (F = 5.5, p = 0.004, Table 2). Importantly, our model indicated that there was an interaction between time, optogenetic stimulation, and MFC inactivation (F = 11.4, p = 0.00001; Table 2).…”
Section: Optogenetic Stimulation Of Mfc Axons In Dms Alters Time-depementioning
confidence: 98%
“…In these rats, both sides of the MFC had been injected with AAV-CamKIIa-ChR2 (MFC-ChR2) and the animals had been implanted with bilateral MFC infusion cannulae and left DMS optrodes. After the rats were acclimatized to infusion and recording procedures, the MFC were bilaterally infused with either saline or the GABA A agonist muscimol, which reversibly and completely inactivates the MFC 13,24,25 .…”
Section: Optogenetic Stimulation Of Mfc Axons In the Dms Normalizes Imentioning
confidence: 99%
See 3 more Smart Citations